Barriers to the development of online shopping in the Klang Valley / Jamaliah Said … [et al.] - Said, Jamaliah; Syed Mohamad, Syed Jamal Abdul Nasir; Mohd Nasir, Noraini; Ghani, Erlane K. (Institute of Education Development (InED), 2007)
Advances in the Internet technology has made it possible to carry out business transactions via the worldwide web. E-commerce, as it is widely known, used to be restricted to business-to-business transactions, but with the approach of the new millennium, the transactions have been expanded to include business-to-consumers. It has brought a whole range of services into information age on a global scale. Improvements in ecommerce has enabled businesses to be conducted across borders and has expedited globalisation. As Malaysia is part of the globalise world, e-commerce should be an important agenda that needs to be addressed. This paper aims to identify the Internet shopping practice among the part-time students in the Klang Valley, Malaysia and also to identify factors that may hinder the development of on-line shopping. The main reasons cited by those who would not shop on-line are the lack of security for credit card payment followed by inability to see the product physically.